Human Rights Violations in Brazilian Prisons and the Role of the Brazilian Supreme Court and of the National Council of Justice (Research, Society and Development, 2022)
This research aims to assess the role of the Brazilian Judicial Power in the protection of human rights in prisons, in the light of the actions of the STF and the ‘National Council of Justice’ (CNJ). Initially, from the division of Powers in the Brazilian State, it is conducted a survey of the competences in the Brazilian State to the management of prisons and to the protection of human rights in prisons; subsequently, it is studied the role of the Judiciary in protecting these rights, based on the analysis of the STF and the CNJ actions. As a result, initially, it was found that the violation of human rights in prisons is not something new in Brazil and it reflects other structural problems in Brazilian society, such as the great social inequality and the systemic racism. This violence is worst to women and to sexual minorities, due to either action or omission from the State institutions. In the end, it was found that the STF has important decisions in favor of the protection of the human rights in prisons; however, some decisions of the same court, which toughen incarceration measures, have had an impact on the worsening of the chaotic situation of the Brazilian prison system. Additionally, the CNJ played an important role in monitoring and promoting the protection of human rights in prisons. The method applied in the development of the research is the inductive method, by which it tries to reach a general conclusion from particular data.